Ecology and plant defense of two invasive plants, Hyoscyamus niger and Verbascum thapsus - Fettig, Christa E., author; Hufbauer, Ruth A., advisor; McKay, John K., committee member; Norton, Andrew P., committee member; Savidge, Julie A., committee member (Colorado State University. Libraries, 2016)
Understanding the factors that drive non-native plant populations to succeed in a new range and the ecological and biological differences that set introduced populations apart from their native counterparts can provide insight into ecological and evolutionary processes, as well as information crucial to management. In this dissertation, I present research on two different plant species that have been introduced to North America, both of which can now be found across the United States and throughout Canada. Chapters 1 and 2 focus on Hyoscyamus niger (black henbane, Solanaceae), a poisonous and state-listed noxious weed. In chapter one I experimentally evaluate whether introduced populations in the western United States are annual or biennial. Both of these life cycles are found in the native range, and have a clear genetic basis. I experimentally manipulated vernalization (a cold treatment for 19 weeks), and find that plants in the introduced range are biennial. Vernalization is critical for bolting and flowering to occur within a growing season. Interestingly, given enough time in a greenhouse setting, 26 percent of plants that were not vernalized were able to flower. This is unlikely to happen in nature, however, as warmer regions without a cold period to naturally vernalize plants are typically lacking sufficient resources (e.g. adequate water or space) for this species. Chapter two aims to understand basic biological and ecological characteristics of black henbane in the introduced range, which lays the groundwork for additional ecological and evolutionary research on this species and will also help direct appropriate management practices. In a greenhouse experiment, I test the effects of selfing and outcrossing. In field populations, I measure reproductive output, the size of seed banks of introduced populations, the viability of seed collected over four years, patterns of mortality, and fluctuation in the size of 15 populations. Black henbane is self-compatible, and capable of producing copious seed, and generating large seed banks in naturalized populations. Seeds remain viable for multiple years which may contribute to the dynamic fluctuations of field population sizes that were observed over four years. Populations are generally ephemeral, with high mortality at the rosette stage. Chapter 3 is focused on resistance and tolerance to herbivory, and how they might vary between ranges as well as within individual plants as predicted by optimal defense theory. Optimal defense predicts that defenses are allocated to different tissues based on their value to the plant. I use Verbascum thapsus (common mullein, Scrophulariaceae) to evaluate resistance to both a specialist and a generalist herbivore among plants from the native and introduced range and among leaves of different ages. I also measure tolerance to defoliation by simulating three levels of herbivory and evaluating the regrowth of above and below ground biomass. Both native and introduced mullein plants are highly defended against specialist and generalist herbivores, with high levels of both resistance and tolerance. In accordance with optimal defense theory, young leaves are more highly defended than older leaves.